1992
DOI: 10.3109/00365529209000167
|View full text |Cite
|
Sign up to set email alerts
|

Symptom Provocation in Irritable Bowel Syndrome Effects of Differing Doses of Fructose-Sorbitol

Abstract: The role of fructose and sorbitol, when ingested together, in the aetiology of irritable bowel syndrome (IBS) is controversial. The aims of this study in IBS patients, therefore, were to compare differences in symptom provocation with various doses of fructose-sorbitol and to relate differences in the extent of colonic hydrogen production after each dose to such symptom provocation. Two different mixtures of fructose and sorbitol--20 g fructose plus 3.5 g sorbitol ('lower' dose) and 25 g fructose plus 5 g sorb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
60
0
1

Year Published

1999
1999
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(64 citation statements)
references
References 20 publications
3
60
0
1
Order By: Relevance
“…In the current study, rats subjected to RS showed an increased relative abundance of Gram-negative bacteria, as well as an increase in LPS levels in the colon, accompanied by mucosal inflammation and impaired gut permeability. These abnormalities are similar to those observed in IBS patients (17,19,20). In the current study, we show for the first time to our knowledge that 2-week LFM prevents the development of mucosal inflammation, impaired permeability, and visceral hypersensitivity evoked by stress.…”
Section: Methodssupporting
confidence: 67%
See 1 more Smart Citation
“…In the current study, rats subjected to RS showed an increased relative abundance of Gram-negative bacteria, as well as an increase in LPS levels in the colon, accompanied by mucosal inflammation and impaired gut permeability. These abnormalities are similar to those observed in IBS patients (17,19,20). In the current study, we show for the first time to our knowledge that 2-week LFM prevents the development of mucosal inflammation, impaired permeability, and visceral hypersensitivity evoked by stress.…”
Section: Methodssupporting
confidence: 67%
“…Ingestion of sugar (lactose or fructose), sorbitol, and oligosaccharides (fructans) alone or in combination may trigger abdominal symptoms (1,17,18). However, the mechanisms responsible for symptom generation in IBS remain poorly understood.…”
Section: Discussionmentioning
confidence: 99%
“…In 1978, Andersson and Nygren [22] first reported cases of fructose malabsorption in which patients received a positive result using the breath hydrogen test. It has been suggested that fructose malabsorption or intolerance occurs more frequently in individuals with compromised gut function as compared with healthy individuals [23,24]. Study by Rao et al [25] revealed that healthy subjects completely absorbed a dose of 15 g fructose.…”
Section: Fructose Malabsorptionmentioning
confidence: 99%
“…The exact mechanisms leading to incomplete fructose absorption are unknown, and in the literature, they are described as ranging from a true condition to a variance of normality [5] . Moreover, it is well established that factors such as dietary sorbitol [6,7] and dietary non-hydrolysable fructans [8] aggravate IBS symptoms [9] . The amount of sorbitol needed to provoke IBS symptoms appears to be ≥ 10 g [10] .…”
Section: Introductionmentioning
confidence: 99%